COVID-19 pandemic: The deadly respiratory disease of 21st century - Shweta Jain; Pankaj Kumar Jain; Ramakant Yadav; Surendra Kumar Jain; Ankur Vaidya (Current Research in Pharmaceutical Sciences, 2021)
The sudden outbreak of 2019 novel coronavirus (2019-nCoV) caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) originated from Wuhan, China. SARS-CoV-2 causes severe respiratory illness and becomes a major threat for humanity. Recently the entire scientist, researchers and physicians all over the countries focused to find the treatment of this pandemic disease. Numerous drugs and or vaccines have been trialed for prevention and treatment against 2019-nCoV but no therapy has been shown effective to date. Currently, numerous vaccines are under clinical investigation and mRNA-1273 vaccine (LNP- encapsulated mRNA vaccine encoding S protein) from Moderna is ahead. Although chloroquine, hydroxychloroquine, remdesivir and many other drugs had recommended against SARS-CoV-2, but still they are not the guarantee treatment of COVID-19. Recently, India, America, Russia and China introduced vaccines against COVID-19 in the market, however assurance of their 100% effectiveness are doubtful. The speed of daily new cases threatens the world and urges the scientist to crack this pandemic condition.